Physical activity recommendations for health: knowledge and perceptions among college students (Recomendaciones de actividad física para la salud: conocimiento y percepciones entre estudiantes universitarios) - Martins, João; Cabral, Miguel; Elias, Cecília; Nelas, Ricardo; Sarmento, Hugo; Marques, Adilson; Nicola, Paulo (Retos, 2019)
Abstract. Every population subgroup should know the physical activity (PA) recommendations to benefit their health. The present study sought to examine the knowledge and explore the perceptions of PA recommendations for adults among Portuguese college students, by gender and fields of study. A total of 255 bachelor students (55.3% women; Mage = 21.0±2.2 years) from sport sciences, health sciences and other fields, from four colleges in Portugal, answered to an online questionnaire. College students’ answers about knowledge of PA recommendations were submitted to an inductive thematic analysis. The chi-square test was used to assess if knowledge of PA recommendations was independent of gender and fields of study. The majority of students (51.0%) assumed not knowing the PA recommendations. From those that assumed to know the PA recommendations, only 9.8% got them right, 42% overestimated, 10.7% underestimated and 37.5% did not know them for other reasons, with no differences found by gender and field of study. Overall, these students fail to identify the minutes per week and the intensity of PA dimensions of the PA recommendations. Portuguese students do not know the PA recommendations for health, including the sports and health sciences students. Implications for the development of national PA recommendations and public health campaigns to improve knowledge of college students are discussed. Resumen. Cada subgrupo de población debe conocer las recomendaciones de actividad física (AF) para beneficiar su salud. El presente estudio buscó examinar el conocimiento y explorar las percepciones de las recomendaciones de AF para adultos entre los estudiantes universitarios portugueses, por género y áreas de estudio. Un total de 255 estudiantes de licenciatura (55.3% mujeres; Medad = 21.0 ± 2.2 años) de ciencias del deporte, ciencias de la salud y otras áreas, de cuatro universidades en Portugal, respondieron a un cuestionario online. Las respuestas de los estudiantes universitarios sobre el conocimiento de las recomendaciones de AF fueron sometidas a un análisis temático inductivo. La prueba de qui-cuadrado se usó para evaluar si el conocimiento de las recomendaciones de AF era independiente del género y de las áreas de estudio. La mayoría de los estudiantes (51.0%) asumieron no conocer las recomendaciones de AF. De aquellos que supuestamente conocían las recomendaciones de AF, solo el 9.8% las acertó, el 42% se sobreestimó, el 10.7% se subestimó y el 37.5% no las conoció por otras razones, sin diferencias por género y área de estudio. En general, estos estudiantes no identifican los minutos por semana y la intensidad de las dimensiones de las recomendaciones de AF. Los estudiantes portugueses no conocen las recomendaciones de AF para la salud, incluidos los estudiantes de deportes y ciencias de la salud. Se discuten las implicaciones para el desarrollo de recomendaciones nacionales de AF y campañas de salud pública para mejorar el conocimiento de los estudiantes universitarios.